High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life

Hexagonal boron nitride quantum dots embedded on layer-by-layer films for peroxidase-assisted colorimetric detection of β-galactosidase producing pathogens - Majumdar, Sristi; Gogoi, Devipriya; Boruah, Purna K.; Thakur, Ashutosh; Sarmah, Priyakhee; Gogoi, Parishmita; Sarkar, Sanjib; Pachani, Priyakshi; Manna, Prasenjit; Saikia, Ratul; Chaturvedi, Vikash; Shelke, Manjusha V.; et al. (ACS Applied Materials and Interfaces, 2024)
Pathogen detection has become a major research area all over the world for water quality surveillance and microbial risk assessment. Therefore, designing simple and sensitive detection kits plays a key role in envisaging and evaluating the risk of disease outbreaks and providing quality healthcare settings. Herein, we have designed a facile and low-cost colorimetric sensing strategy for the selective and sensitive determination of beta-galactosidase producing pathogens. The hexagonal boron nitride quantum dots (h-BN QDs) were established as a nanozyme that showed prominent peroxidase-like activity, which catalyzes 3,3 `,5,5 `-tetramethylbenzidine (TMB) oxidation by H2O2. The h-BN QDs were embedded on a layer-by-layer assembled agarose biopolymer. The beta-galactosidase enzyme partially degrades beta-1,4 glycosidic bonds of agarose polymer, resulting in accessibility of h-BN QDs on the solid surface. This assay can be conveniently conducted and analyzed by monitoring the blue color formation due to TMB oxidation within 30 min. The nanocomposite was stable for more than 90 days and was showing TMB oxidation after incubating it with Escherichia coli (E. coli). The limit of detection was calculated to be 1.8 x 10(6) and 1.5 x 10(6) CFU/mL for E. coli and Klebsiella pneumonia (K. pneumonia), respectively. Furthermore, this novel sensing approach is an attractive platform that was successfully applied to detect E. coli in spiked water samples and other food products with good accuracy, indicating its practical applicability for the detection of pathogens in real samples.
Keywords: biopolymer; colorimetric; h-BN quantum dots; nanozyme; pathogens; Sensor